Pott’s Disease during Pregnancy – A Physical Medicine and Rehabilitation Approach to Improve Function: A Case Report - Agus Prasetyo; Fatchur Rochman (Indonesian Journal of Physical Medicine & Rehabilitation, 2014)
Objective: To assess the role of physical medicine and rehabilitation (PM&R) in an interdisciplinaryteam approach in managing a pregnant woman with Pott’s disease.Methods: A 24 year-old female in her 31st week of pregnancy (G2P0A1) with a diagnosis ofC4 tetraplegia AIS C and accompanying problems such as, premature ruptured of membrane,spondylitis tuberculous, cardiovascular compliance changes, weakness of all limbs, sensory deficit,severely dependent ADL (Barthel Index 60), and moderate depression. She was managed by aninter-disciplinary team. The short-term goals were saving the infant, protecting the spinal cordand its function and improving the psychological condition. The ultimate rehabilitation goals wereindependent ambulation, independent ADL, which increases the quality of life and helping her getback to work. Rehabilitation management included cervico-thoracal orthoses with FELR control forvertebral immobilization, mobilization exercises, active breathing exercises, ROM exercises of allof her limbs, improving cardiovascular endurance and sensory re-education.Results: During conservative therapy, the patient used a cervical collar brace and tuberculous drugscategory 1 except streptomycin. A caesarean section was performed on May 24th, 2013, followedby operative decompression and vertebral stabilization procedure with a pedicle and screw 1 weekafter (May 31st, 2013). Afterwards, the patient used cervico-thoracal orthoses with FELR control forvertebral immobilization. The histologic examination showed granulomatous inflamation supportedSpondylitis tuberculous. Within 3 months of physical medicine and rehabilitation management,the Barthel Index, which was initially 60 (Severe dependent Activity Daily Living/ ADL), became100 (independent ADL). Physical Medicine and Rehabilitation management included mobilizationexercises, active breathing exercises, ROM exercises of all of her limbs, improving cardiovascularendurance and sensory re-education. Overall, the increased quality of life of this patient reflected thesuccessful inter-disciplinary team management.Conclusion: The PM&R approach in the interdisciplinary team resulted in an optimal functionalrecovery of the patient with Pott’s disease during pregnancy.Keywords: Pott’s disease, pregnancy, physical medicine and rehabilitation, function